Is Social Contact With the Resident Population a Prerequisite of Well-Being and Place Attachment? The Case of Refugees in Rural Regions of Germany - Glorius, Birgit; Kordel, Stefan; Weidinger, Tobias; Bürer, Miriam; Schneider, Hanne; Spenger, David (Frontiers in Sociology, 2020)
Due to dispersal policies applied in many European countries such as Germany, rural regions are important arrival regions for asylum seekers and refugees. For German policy makers, who have faced a large number of immigrants since 2015, it is crucial that asylum seekers and refugees stay in those rural regions and benefit the development of those areas. This paper addresses the quality and quantity of social contact between refugees and resident populations as a prerequisite for integration and long-term migration-development effects from a social geographical perspective. Drawing from survey data and qualitative interviews, we examine expectations, perceptions and experiences of everyday encounters and social relationships in neighborhoods in small rural towns and villages from the perspective of both local residents and refugees. Our results support arguments from research literature for faster social inclusion in rural areas due to greater nearness, but also obstacles toward the integration of foreigners due to a higher homogeneity of rural neighborhoods and only few experiences of positive everyday contact with foreigners among rural residents. The interviewed refugees display a high level of reflexivity regarding their new neighborhood and how they might be seen by rural residents. Their experiences encompass various forms of social relationships, while social bridges are crucial, ranging from serendipitous encounters and functional interactions to connections based on mutual interest around family issues or cultural aspects. Openness and tolerance from at least some parts of the local population can help immigrants to feel at home, and support staying aspirations, while simultaneously evoking wider social change. A peculiarity of rural areas is the intersectionality with further challenges related to structural changes, encompassing, for instance, socio-demographic and economic restructuring. However, social interactions and opportunities for encounters are only one factor in the development of long-term settlement. More in-depth research is needed to consider the interrelations of both structural contexts and complex and changing needs for personal development in the future, also from an intergenerational perspective.